2021
DOI: 10.1038/s41598-021-02336-6
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal personality traits and the social learning of fear

Abstract: Schizotypy can be defined as a combination of traits qualitatively similar to those found in schizophrenia, but milder in their expression, that can be found in clinical and non-clinical populations. In this research, we explore, to our knowledge, for the first time, whether schizotypal personality traits may affect the acquisition of conditioned fear by social means only. Apart from being an essential capacity to ensure learning in safe environments, social fear learning shares important characteristics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…During the test phase, we replicated the general SFL effect (Espinosa et al, 2020; González‐Rodríguez et al, 2021) but also found an interaction between CS and group such that only healthy controls showed a higher SCR in response to the CS+ compared to CS−. This important result indicates significant learning in the control group and nonexistent learning in the patients with severe AUD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During the test phase, we replicated the general SFL effect (Espinosa et al, 2020; González‐Rodríguez et al, 2021) but also found an interaction between CS and group such that only healthy controls showed a higher SCR in response to the CS+ compared to CS−. This important result indicates significant learning in the control group and nonexistent learning in the patients with severe AUD.…”
Section: Discussionsupporting
confidence: 80%
“…This task was chosen because it is a reliable and sensitive paradigm to evaluate social learning. Indeed, this paradigm has been used recently among persons with mental health disorders such as autistic spectrum disorder (Espinosa et al, 2020) or schizotypal personality (González-Rodríguez et al, 2021).…”
mentioning
confidence: 99%
“…Here, we used the PGT to test for behavioral evidence of hyperexcitability as a function of schizotypy symptomatology in thenon-clinical population. Schizotypy refers to individuals in the general population that vary in schizotypal traits (Broyd et al, 2016;González-Rodríguez et al, 2021;Kwapil & Barrantes-Vidal, 2015). The non-clinical population is appealing because it avoids concerns related to the effects of antipsychotic medications (see Ettinger et al, 2015 for review; Kelemen et al, 2013), high schizotypy individuals have similar sensory profiles to SSD (Broyd et al, 2016;Moussa-Tooks et al, 2021;Myles et al, 2017;Nelson et al, 2013), and they are accessible.…”
Section: Current Studymentioning
confidence: 99%
“…Here, we used the PGT to test for behavioural evidence of hyperexcitability as a function of schizotypy symptomatology in the non‐clinical population. Schizotypy refers to individuals in the general population that vary in schizotypal traits (Broyd et al, 2016; González‐Rodríguez et al, 2021; Kwapil & Barrantes‐Vidal, 2015). The non‐clinical population is appealing because it avoids concerns related to the effects of antipsychotic medications (see Ettinger et al, 2015 for review; Kelemen et al, 2013), high schizotypy individuals have similar sensory profiles to SSD (Broyd et al, 2016; Moussa‐Tooks et al, 2021; Myles et al, 2017; Nelson et al, 2013), and they are accessible.…”
Section: Introductionmentioning
confidence: 99%